Effects of translanguaging on science literacy among high school students - Guinto, Christian Genesis (American Journal of STEM Education, 2026)
This study examined the effects of translanguaging on science literacy among Grade 10 students in a multilingual Philippine classroom. Seventy-eight participants were assigned to a translanguaging instruction group (n=39), integrating Filipino and English, or a monolingual instruction group (n=39). ANCOVA results showed significantly higher post-test science literacy scores for the translanguaging group (adjusted M=37.21, SE=0.64) than the monolingual group (adjusted M=29.13, SE=0.64), F(1,75)=79.64, p